Population genetic structure of Pomacea canaliculata in China based on the COI and ITS1 genes - Wei, Ran; Chang, Ya-Wen; Xie, Hong-Fang; Wu, Cheng-dong; Yuan, Deng-Rong; Gong, Wei-Rong; Du, Yu-Zhou (Scientific reports, 2024)
Comprehending the phylogeography of invasive organisms enhances our insight into their distribution dynamics, which is instrumental for the development of effective prevention and management strategies. In China, Pomacea canaliculata and Pomacea maculata are the two most widespread and damaging species of the non-native Pomacea spp.. Given this species’ rapid spread throughout country, it is urgent to investigate the genetic diversity and structure of its different geographic populations, a task undertaken in the current study using the COI and ITS1 mitochondrial and ribosomal DNA genes, respectively. The result of this study, based on a nationwide systematic survey, a collection of Pomacea spp., and the identification of cryptic species, showed that there is a degree of genetic diversity and differentiation in P. canaliculata , and that all of its variations are mainly due to differences between individuals within different geographical populations. Indeed, this species contains multiple haplotypes, but none of them form a systematic geographical population structure. Furthermore, the COI gene exhibits higher genetic diversity than the ITS1 gene. Our study further clarifies the invasive pathways and dispersal patterns of P. canaliculata in China to provide a theoretical basis.